The development of an IRAF-based scientific photometric package for the UFS-Boyden 1.5-m telescope - Van Heerden, Hendrik Jacobus (University of the Free State, 2009)
In this dissertation there will be looked at the development of an (Image Reduction and Analysis Facility) IRAF-based scientific photometric package for the UFS / Boyden 1.5-m telescope. The dissertation consist of a discussion on the history of Boyden Observatory and its instruments, with specific emphasis on the Rockefeller 1.5-m telescope. The discussion will include information on the upgrades and improvements the telescope underwent to compete and do research on an international level. In the proceeding chapters charged coupled devices (CCDs) will be discussed, as well as how to characterize CCD photometric observation systems, like the 1.5-m telescope. The chapters will include experimental procedures and results obtained during characterization experiments. Chapters on photometry techniques will follow thereafter as well as the development of the Boyden-IRAF photometric data-analysis system. It will include an overview of IRAF, as well as a more in depth discussion of the Boyden-IRAF package. The discussion will specify as to why and how it was developed and how it works. A final chapter will be presented on the testing of the Boyden-IRAF package through the determining of the Boyden atmospheric extinction coefficients using the newly developed package. With this project, i.e. the development of an IRAF-based photometric program, an attempt is made to fill a void that exists related to the in-house photometric capabilities. A reliable and user-friendly photometric program will definitely also result in Boyden Observatory playing an important role in student training and research programs. Finally a conclusion will be drawn as to the success of the new developments, the IRAF-based photometric package, and what this means for the development of Boyden Observatory and the UFS Astrophysics group i.t.o. research and development.

In hierdie verhandeling sal daar verwys word na die ontwikkeling van ’n (Image Reduction and Analysis Facility) IRAF-gebasseerde wetenskaplike fotometriese pakket vir die UV/Boyden 1.5-m teleskoop. Hierdie verhandeling sal bestaan uit ’n bespreking van die geskiedenis van die Boyden Sterrewag en die instrumente wat daar gestasioneer is, veral die Rockefeller 1.5-m teleskoop. Die bespreking sal bestaan uit inligting oor die opgradering en verbeterings wat die teleskoop ondergaan het om dit in staat te stel om te kan kompeteer en navorsing te doen op ’n internasionale vlak. In die daaropeenvolgende hoofstukke sal ”Charged Coupled Devices” (CCDs) bespreek word, en die metode om CCD fotometriese sisteme te karakteriseer, byvoorbeeld die 1.5- m teleskoop. Hierdie hoofstukke sal eksperimentele prosedures en resultate, verkry vanaf karakteriserings eksperimente, bevat. ’n Verdere hoofstuk oor fotometriese tegnieke sal volg, asook ’n hoofstuk oor die ontwikkeling van die Boyden-Iraf fotometriese data-analise sisteem. Dit sal ’n oorsig van IRAF, en ’n meer in-diepte bespreking van die Boyden-IRAF pakket, insluit. Die bespreking sal spesifiseer hoekom en hoe dit ontwikkel is en hoe dit werk. ’n Finale hoofstuk sal handel oor die toetsing van die Boyden-IRAF pakket deur die Boyden atmosferiese uitdowings ko¨effisiente te bepaal, deur gebruik te maak van hierdie pakket. Met hierdie projek word ’n leemte gevul met betrekking tot die interne fotometriese navorsing vermo¨ens. ’n Betroubare en verbruikersvriendelike fotometriese program sal definitief ook daartoe bydra dat Boyden Sterrewag ’n belangrike rol speel in studente opleiding en navorsingsprogramme. Aan die einde sal ’n gevolgtrekking gemaak word wat handel oor die sukses van die nuwe ontwikkelings, die IRAF-gebasseerde fotometriese pakket, en hoe hierdie projek sal bydra tot die ontwikkeling van die Boyden Sterrewag en die UV Astrofisika-groep, in terme van navorsing en ontwikkeling.
Dissertation (M.Sc. (Physics))--University of the Free State, 2008
Keywords: Imaging systems in astronomy; Image processing; Astronomy; IRAF; Atmospheric Extinction Coefficients; Boyden Observatory; Photometric pipeline; Rockefeller telescope; CCD photometry